The impact of technological advancement on total factor productivity of cotton: A comparative analysis between Pakistan and India - Malik Shahzad Shabbir; Nusrat Yaqoob (Journal of Economic Structures, 2019)
Pakistan and India are the two major producers of the cotton, the most demanding crop of the world which is known as white gold. However, for some recent years, it deems that Pakistan's share in the international textile market dwindles compared to India. Thereby, the study will investigate whether the productivity of the crop per hectare is the reason or area of the crop, in the countries which lead to a higher share of India in the international market. In addition, which country has a comparative advantage in terms of cotton yield kg per hectare, particularly due to technological advancement in India and Pakistan's agriculture sector? And this study also examines which country has exploited natural and technological inputs most. The time-series data from 1954 to 2017 have been used in this study, the results of the study are drawn using two-stage analysis. At first, we get total factor productivity (TFPCc) for both the countries using Tornqvist-Theil Index: total factor productivity input-output method. Then, the obtained variable has been employed as a regress and variable on farm and non-farm regressors. The ARDL: autoregressive distribution lag regression model has been applied on [area of cotton, fertilizer consumption kg/ha, high yield varieties (HYV) seeds, electricity consumption in agriculture sector, agriculture labor force, and irrigation by canal water and tube well water, besides tractors] to find the technological advancement impact on the TFPC of cotton. The results explore that overall improvement in farm inputs has a more stable impact on the productivity of cotton in Pakistan, whereas HYV seeds, mechanization, and area are the real reason for the growth in India.
Keywords: 330; Cotton; Technological advancement; Total factor productivity; Pakistan and India